SIMULATION OF CLIMATE CHANGE EFFECT ON RICE (Oryza sativa L.) PRODUCTION IN KANO RIVER IRRIGATION SCHEME (KRIS) USING APSIM MODEL (FUDMA JOURNAL OF SCIENCES, 2023)
Climate change threatened rice production in the semi-arid region of Nigeria. Agricultural production is affected by variations in weather conditions and long-term climate patterns. The pattern of changing climate in the last three decades indicated that changes in rainfall and temperature reduced agriculture outputs and yields, which is significant in rice. A farm experiment was set up with six cultivars of rice. The APSIM model was used to simulate grain yield at maturity under a change in temperature scenarios to observe the effect of climate change on rice. Results showed that the mean annual temperature in KRIS has risen by about 0.62 degrees in a decade, while a rise of 0.9 degree Celsius between “2010-2040” respectively. Also, there was no significant difference in the measured yield between the rice varieties, however, their response to a change in temperature in the simulated yield is significant. effect of decreased temperature on the rice yield within the span of two decades and were simulated under 1 oC, 2 oC, and 3oC rise in temperature. The overall yield is decreasing steadily and began to descend by 2025, in 2038 the yield began to rise again which was not clear as to the reason for the rise. However, on average there was a generally decreased yield over the two decades. It was recommended that a climate change adaptation strategy such as growing high yield short duration of rice variety to reduce the impact and ensure food security.
Keywords: APSIM; Climate Change; KRIS; Simulation; Rice